Lacan and Chan Buddhist thought : reflections on Buddhism in Lacan's Seminar X and beyond /: reflections on Buddhism in Lacan's Seminar X and beyond. (2022) - Moncayo, Raul; Yu, Yang; Han, Sora
No abstract available